The gens and Intestate Inheritance in the Early Republic*. (26th October 2017) - Bartlett, Charles
Abstract: This paper attempts to gauge the ability of the gens to influence the affairs of its members by tracing the development of the rules governing intestate inheritance. It will argue that, although the power of the gens in this area of the law did eventually give way to a more centralised and stronger state, a development which has been documented in other areas of Roman society as well, the gens was nonetheless able to continue to exert an influence on its members for some considerable time. The present study will analyse several cases to argue this point and examine both the means by which this centuries-long change took place, as well as highlight a period that witnessed a potential acceleration of the trend away from gentilicial importance. Finally, it will return to the circumstances of early Rome, the focal point for this volume, and offer some cautionary notes for thinking about the period that was in many ways the starting point for these developments.